Bilateral sterile subdural effusion in Kawasaki disease-A case report - Nicolescu, Corina Ramona; Duperril, Marie; Stephan, Jean-Louis (Frontiers in Pediatrics, 2022)
Kawasaki disease is an acute febrile condition that causes a self-limiting medium vessel systemic vasculitis and whose pathophysiological pathways are still not completely understood. Coronary arteries are the most affected, but inflammation can develop in all medium-sized arteries, with various organs and tissues being involved during the acute febrile phase, and consequently with variable clinical features. Kawasaki disease-related neurological involvement varies in terms of clinical expression and severity. Herein, we describe an unusual neurological complication of Kawasaki disease in a 5-year-old girl. The progression of the disease was biphasic. Kawasaki disease was diagnosed on the 8th day after symptoms onset and treated by intravenous immunoglobulins, with prompt clinical regression but a less favorable biological response (persistent inflammation with hypoalbuminemia). Two weeks later, headaches and lethargy developed, and a bilateral subdural collection was identified on cerebral imaging. Subsequently, her progress was uneventful, with no residual coronary abnormalities and complete resorption of the subdural collection. Bilateral subdural collection, exceptionally reported, could be discussed as a clinical expression of systemic inflammatory vasculitis that characterizes Kawasaki disease.